Development of Interactive Java Language Learning Module in Object Oriented Programming Subjects - Devega, Army Trilidia; Irfan, Dedy; Wakhinuddin, Wakhinuddin; Muskhir, Mukhlidi; Jasman, Muhammad Ikram (FKIP Universitas Lampung, 2021)
The purpose of this research is to develop interactive learning modules that can help students in independent learning and are valid, practical, and effective. This research was carried out using the Research and Development (R&D) development research method with a 4D (four D) development model. The instrument used in this study was a questionnaire used to measure validity and practicality. Meanwhile, to measure the effectiveness of using a test instrument in the form of multiple choice questions. The results showed that the interactive learning module was declared valid with a validity value of 0.88 based on the validation of three media validators and in terms of material validity it was declared valid with a value of 0.89 from two teachers who taught object oriented programming (OOP). The interactive learning module is stated to be very practical based on the responses of teachers and students. This shows that the interactive learning module is declared to be effectively used as one of the teaching materials in learning in improving student learning outcomes.Keywords: interactive learning module, object oriented programming, research and development. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp235-244